Validation of QTLs for Eating Quality of Japonica Rice ‘Koshihikari’ Using Backcross Inbred Lines - Takuya Wada; Hideshi Yasui; Takashi Inoue; Masao Tsubone; Takefumi Ogata; Kazuyuki Doi; Atsushi Yoshimura; Yuji Matsue (Plant Production Science, 2013)
Using backcross inbred lines (BILs) derived from a cross between temperate japonica rice cultivars, Moritawase and Koshihikari, we validated the major quantitative trait loci (QTL) for eating quality and textural characteristics on chromosomes (Chr) 1, 2, 3, 6, 7, 10, and 12. Significant genetic differences in eating quality among BILs were detected at the QTL on Chr 3 and corresponded to the differences between the parents. Although differences in eating quality on the other chromosomes were not significant by t-test, cluster analysis and principal component analysis clearly showed that the genetic effects of the QTLs on Chr 6, 7, and 10 were similar to that on Chr 3, but the genetic effects of QTLs on Chr 1, 2, and 12 were entirely different from that on Chr 3. We previously identified that textural characteristics were highly correlated with eating quality. In this study, genetic differences in textural characteristics were similar to the genetic differences in eating quality among BILs. These results reveal major QTLs for eating quality of Koshihikari on Chr 3, 6, 7, and 10. The QTL on Chr 3 contributed most to the improvement of eating quality and textural characteristics.